Hinterlands to cities: the archaeology of northwest Mexico and its vecinos - Pailes, Matthew C., author; Searcy, Michael T., author; The SAA Press, publisher (Colorado State University. Libraries, 2022)
This approachable book is a comprehensive synthesis of Northwest Mexico from the US border to the Mesoamerican frontier. Filling a vital gap in the regional literature, it serves as an essential reference not only for those interested in the specific history of this area of Mexico but western North America writ large. A period-by-period review of approximately 14,000 years reveals the dynamic connections that knitted together societies inhabiting the Sea of Cortez coast, the Sonoran and Chihuahuan deserts, and the Sierra Madre Occidental. Networks of interaction spanned these diverse ecological, topographical, and cultural terrains in the millennia following the demise of the megafauna. The authors provide a fresh perspective that refutes depictions of the Northwest as a simple filter or conduit of happenings to the north or south, and they highlight the role local motivations and dynamics played in facilitating continental-scale processes.--Provided by publisher.
Introduction to the northwest -- Paleoindian period -- Archaic period -- Regional traditions -- Exchange and warfare: regional interaction in the late precolonial period -- Religious ideology in the northwest -- Colonial period archaeology.
Keywords: Mexico, North -- Antiquities; Mexico, North -- History